Case report: Flail leg syndrome in familial amyotrophic lateral sclerosis with L144S SOD1 mutation - Zapalska, Ewa; Wrzesień, Dominika; Stępień, Adam (Frontiers in Neurology, 2023)
We observed a Polish family with familial amyotrophic lateral sclerosis with heterozygous L144S SOD1 mutation, which manifested clinically as flail leg syndrome. Flail leg syndrome is a rare phenotype of amyotrophic lateral sclerosis, with slow progression, long survival, and predominance of lower motor neuron signs at onset, as a triad of distal paresis, muscle atrophy, and hyporeflexia/areflexia, confined to the lower limbs for an extended period of time. Although familial amyotrophic lateral sclerosis is usually associated with a worse prognosis than the sporadic form of the disease, the clinical course of the disease in patients with L144S SOD1 mutation is benign, with slow progression and long survival. This unique case report provides an in-depth clinical analysis of all of the symptomatic members of a family, who were diagnosed with amyotrophic lateral sclerosis in our clinic, including three siblings (two brothers and a deceased sister) with flail leg syndrome and their fraternal aunt, who has been previously misdiagnosed with cervical myelopathy and is living with symptoms of the disease for 15 years. Sanger sequencing of the SOD1 gene was performed in all of the living patients, revealing an L144S (c.434T>C, p.Leu145Ser) heterozygous mutation. The aim of this case report is to increase the physician's awareness of the atypical phenotypes of amyotrophic lateral sclerosis and hopefully, to encourage further research on the factors responsible for delayed disease progression in patients with L144S SOD1 mutation.